Neuronal cell death in the amygdala and cerebral cortex of mice (Mus musculus) induced by bee (Apis mellifera) venom - Rian Oktiansyah; Ummi Hiras Habisukan; Anggun Wicaksono; Yustina Hapida; Fahmy Armanda (Biogenesis: Jurnal Ilmiah Biologi, 2023)
Brain is an organ to control our activities, such as human consciousness, emotional, and movement. It was controlled by amygdala and cerebral cortex as the parts of the brain. Many things that can bring over it. Bee venom (BV) is known as traditional medicine and probably can sway the brain. The objective of this study was to determine the dose of BV that causes excessive neuronal cells death, especially in the amygdala and cerebral cortex. About 15 white male mice Deutsch Denken Yoken (DDY) strain were divided into control group and the treatment group. BV was administrated intraperitoneally for two weeks with multilevel doses, that was 1.88 mg/kg, 3.76 mg/kg, 5.6 mg/kg, and 7.48 mg/kg. Brain tissue isolation was performed three days of the last administration by using perfusion method. Morphological sectioned of brain tissue (amygdala and brain cortex) was stained by hematoxylin-eosin (HE). The results indicated that the BV inclined to affect neuronal cells death in the amygdala and cerebral cortex. Based on the study, the highest doses (7.48 mg/kg) of BV caused the highest neuronal cell death.